Application Of The Jigsaw Cooperative Learning Model To Improve The Learning Outcomes Of Civic Education Of 8th Grade Students In SMPN 9 Kota Sorong - Lawatta, Esterlina H. (Sains Global Institut, 2019)
This research is a classroom action research that aims to see whether there is an influence of the application of the Jigsaw cooperative learning model in an effort to improve the learning outcomes of Civics. The subjects in this study were students of class VIII-3 at SMP Negeri 9 Sorong City in the academic year 2017/2018 with a total of 30 students consisting of 13 male students and 17 female students. This CAR procedure consists of 2 cycles with 2 meetings per cycle. Each cycle consists of four stages as follows: 1) planning; 2) implementing actions; 3) observation and evaluation of actions; and 4) reflection of actions. The research data used the learning achievement test instrument, student worksheets and observation sheets. Data obtained from the results of the test, both at the beginning of the test and at the end of each cycle are processed using descriptive statistics. Statistical techniques to describe student characteristics and results are presented in the form of the highest value, lowest value, average value and frequency distribution table. The results of the study show that: (1) Quantitatively the learning outcomes of citizenship education on the concept of popular sovereignty in class VIII-3 students, SMP Negeri 9 Sorong City after the implementation of the first cycle action through the application of jigsaw cooperative learning is categorized as moderate with an average value of 47.5 with an average classical completeness of 43.34% and after the implementation of the second cycle is categorized well with an average value of 72.84 with an average classical completeness of 96.67%; (2) Qualitatively, there was a good increase from cycle I to cycle II with the percentage of permanent student attendance from 100%, the percentage of students paying attention to subject matter increased from 90% to 98.34%, the percentage of students who asked questions about material that had not understood decreased from 48.34% to 8.34%, the percentage of students working on practice questions / answering questions increased from 84.98% to 100%.